A construção da personagem na Revista Piauí : uma perspectiva ética da tessitura da identidade narrativa de Francenildo nas textualidades biográficas do jornalismo - Joyce Athie da Costa (2015)
This paper aims to investigate the ethical tensions involved in the operation of making a source into a character, made by an author the journalist. For this research, we will analyze three profiles published in the magazine piauí, written by João Moreira Salles, namely “O Caseiro” (Ed 25, October 2008.), which unfolds in two other publications: “Crime e reparação” (Ed. 37, October 2009) and “O processo” (Ed. 96, September 2014). We will investigate dialogical and polyphonic relations of the narrative voices, investigating to what extent the reports, seen here as biographical spaces, contribute to shaping the character of narrative identity from the specificities of the magazine. As theoretical support of this investigation, we will seek references about biographical space and the illusion that this carries with Leonor Arfuch (2010) and Pierre Bourdieu (2002). With the French philosopher Paul Ricoeur (1913 2005), we seek the understanding of the narrative theory and the identity of the subjects. About narrative construction, instigates us the reflection of the present voices and the relationships established between them. Therefore, also appealed to the theoretical language, Russian Mikhail Bakhtin (18951975), who will discuss some key concepts, especially the concept of polyphony, dialogism and ethics. Thus, the perspective of the constitution of subjects through narratives, added to the concepts analyzed regarding the biographical space, leads us to compose the following analytical operators to realize the narrative analysis of our object of study: the narrative identity, polyphony, biographical values and ethics.